Optimizing Parenting Program in an effort of building Character Education Children In early childhood “Permata Hati” Kadipiro Surakarta - Feri Faila Sufa & M. Hery Yuli Setiawan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Feri Faila Sufa, M Hery Yuli Kurniawan. Optimizing Parenting Program in an effort to Building CharacterEducation In early childhood “Permata Hati” Kadipiro Surakarta. Beside through formal education (kindergarten,RA) Early Childhood Education (ECE) is also done through education in the family (informal education), andeducation in the community (non-formal education) play groups and another of early childhood (SPS), such as atSunday school, ECE unit similar, Education Park Village In Al-Qur'an, and others. The beginning of pre-schooleducation is not only the responsibility of teachers, but also parents and a society. Optimizing the empoweringrole of parents through parenting is done so that is synergistic with the vision and mission of early childhoodprograms. Efforts to internalize the character education of children through parenting activities. Based on thesurvey that conducted in Pos of early childhood Education Permata Hati Kadipiro, show that parenting programis not running optimally. Evidently from many parents are in class, when the learning process takes place, in theoutside of classroom seems some kids do not join the learning process because they follow their parents, besidesome parents huddle outside the classroom for waiting their children/childs without any activity, so there is noproductive activity or no ideas to help the early childhood program at the school. The method that used is to giveassistance parenting activities, form the organizational structure of the parents. The results show that the assistancethrough coordinated parenting activities every month to make parents become more productive, and understandthe importance of children's education in instilling character education from an early age.Keywords: Character Education, Parenting, Early Children Education (ECE).